2017
DOI: 10.1111/idh.12311
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a preschool preventive dental programme on caries prevalence, oral care and secretory immunity to Streptococcus mutans in young adults

Abstract: Preventive programmes for preschool children positively impact on DMFS and periodontal status in young adults, but have no long-term effects on dietary or hygiene habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Noticeably, another strategy could be the adoption of preventive programmes for preschool children, that, in some cases, have been demonstrated to positively impact on DMFT and periodontal status in young adults. 42 It seems to be obvious, but being the caries experience still too high, it means that we have to work harder to promote and strengthen interdisciplinary collaboration among families, teachers, paediatricians and dentists, to reduce the onset of caries, their delayed diagnosis and the related repercussion on quality of life of the children, 43 together with the development of adjunct non-invasive methods in caries detection. [44][45][46] 5 | CLINIC AL RELE VAN CE…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noticeably, another strategy could be the adoption of preventive programmes for preschool children, that, in some cases, have been demonstrated to positively impact on DMFT and periodontal status in young adults. 42 It seems to be obvious, but being the caries experience still too high, it means that we have to work harder to promote and strengthen interdisciplinary collaboration among families, teachers, paediatricians and dentists, to reduce the onset of caries, their delayed diagnosis and the related repercussion on quality of life of the children, 43 together with the development of adjunct non-invasive methods in caries detection. [44][45][46] 5 | CLINIC AL RELE VAN CE…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the dental first examination cannot be avoided nor delayed and, since “prevention is better than treatment,” strongest campaigns among parents and paediatricians are needed to allow the spread of the knowledge about bad oral hygiene habits, caries risk factors and the need for early screening. Noticeably, another strategy could be the adoption of preventive programmes for preschool children, that, in some cases, have been demonstrated to positively impact on DMFT and periodontal status in young adults 42 …”
Section: Discussionmentioning
confidence: 99%
“…The presence of material on the surface of pits and fissures of teeth decreases the retention of food in the place and facilitates the hygiene, reducing the risk of developing dental caries in these areas 10.13 . Educational-preventive programs of dental care assistance for children since birth promote oral health education and perform preventive procedures in the Odontopediatrics context [18][19][20] . In addition to careful anamnesis and clinical examination, orientation activities of diet, oral hygiene instruction, control of dental biofilm and topical application of fluoride are commonly performed in programs for the prevention of dental caries 18,19,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Educational-preventive programs of dental care assistance for children since birth promote oral health education and perform preventive procedures in the Odontopediatrics context [18][19][20] . In addition to careful anamnesis and clinical examination, orientation activities of diet, oral hygiene instruction, control of dental biofilm and topical application of fluoride are commonly performed in programs for the prevention of dental caries 18,19,21 . However, the use of sealants of pits and fissures as preventive procedure is not commonly adopted 12,22,23 , and few studies have demonstrated the importance of the use of sealants in deciduous dentition 22.24 .…”
Section: Introductionmentioning
confidence: 99%